Portrait of Community Dynamic Changes Towards Globalisation Development - Sukron Azhari; Masroer (ASTEEC, 2023)
The dynamics of social change in society is a reality that occurs in people's lives, especially in Wakan Village, especially with the current rapid development of globalization. The development of globalization is a new challenge for all levels of society, especially those that are able to give effect to old habits to be abandoned. Globalization in people's lives has positive and negative impacts in all aspects of change. However, from the impact caused by the current development of globalization, it becomes a challenge for the community to learn about introjection caused by the development of globalization. Therefore, people must have knowledge and be wise in carrying out an era development, especially with the progress of globalization. Adopting a development of globalization wisely will be able to provide benefits for every community life, but apart from the benefits obtained in adopting the development of globalization by the community, the positive values ​​that were previously carried out are also not spared. So that people do not become ambiguous towards the customary values ​​that they used to have.